Competitiveness and Factors Influencing Indonesian Clove Exports to Eight Export Destination Countries from 2005-2020 - Siti Ainia Hidayati; Ekaria (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Indonesia is the largest clove producer and exporter in the world, but from 2005 to 2020 the average clove export was dominated by Madagascar. As the largest clove producer, Indonesia should be able to dominate the export market, especially cloves. Therefore, this study aims to determine the competitiveness position of Indonesian cloves and analyze the economic factors that affect Indonesian cloves exports. In this study, the analysis method use Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and a Fixed Effect Model (FEM) for panel data of eight export destination countries from 2005-2020. The results show that the competitiveness of Indonesian cloves is above the world average. The competitive position of Indonesia's clove exports in the Netherlands, Pakistan, Saudi Arabia, United Arab Emirates, United States, and Vietnam is a rising star. At the same time, the other two markets (India and Singapore) are falling stars. In addition, the export prices have a significant effect on the volume of Indonesian clove exports. Indonesian clove production and destination countries' GDP per capita have a positive effect, while economic distance has a negative effect on the volume of Indonesian clove exports.